Carga de fratura de cantiléveres de protocolos mandibulares confeccionados por meio de duas formas alternativas - Brant Filho, Adalberto Caldeira (2014)
The aim of this study was to evaluate the mechanical strength of cantilevers manufactured in two alternative ways: by the process of welding using voltaic arc with argon, welder TIG (n=10) and prefabricated Neodent® (Curitiba, PR, Brasil) Distal Bar (n=10), compared to the currently more adopted model, which is cobalt chrome bar (Co-Cr) fused and welded (n=10). All samples were subjected to loading test in universal testing machine (EMIC 2000DL São José dos Pinhais -PR, Brazil). The data were analyzed by variance of analysis to verify statistical differences among groups (α=5%), Tukey s test was chosen for group analysis. We observed statistical differences among fused and welded group Co-Cr (1617,800 ± 285,160 N) in comparison to TIG (520,360 ± 199,193 N) and Neodent Distal Bar (592,200 ± 105,014 N), there was not statistical difference between groups TIG and Barra Distal Neodent® (Curitiba, PR, Brasil). It was concluded that the alternative techniques present strength compatible to masticatory stress and can be used in manufacturing of metal frameworks in oral rehabilitation of edentulous patients, once the occlusal loading is favorable and has a small cantilever, the observed difference suggests that clinical conditions that requires large loadings still must be resolved with traditional bar.